Antagonis Soluble Fms-Like Tyrosine Kinase 1 (sFlt-1) dan Soluble Endoglin (sEng) pada Preeklamsia - Mohd Andalas; Harahap Harahap (Fakultas Kedokteran Universitas Riau, 2010)
Proangiogenic factor signal transduction like vascular endothelial growth factor (VEGF), placental growth factor(PlGF) and tissue growth factor â-1 (TGFâ-1) are important to angiogenesis and vascular health in pregnancy. Inpreeclampsia (PE) concentration of fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng) are increasesignificantly. Base on analysis from resent research shown that sFlt-1 and sEng inhibit angiogenic factor signaltransduction by competition - in result angiogenic factor can‘t bind to their receptor. sFlt-1 and sEng are potential usedas preeclampsia therapy because sFlt-1 and sEng have main role in PE pathogenesis. We suggest that the research tofind out effective sFlt-1 and sEng antagonist have to conduct in the next time.